THE EFFECT OF USING THE YANBU'A METHOD ON THE ABILITY TO READ THE AL-QUR'AN SANTRI IN PONDOK PESANTREN AL-BADAR KECAMATAN PAMIJAHAN BOGOR - Agus Sarifudin; Nana Ernawati (Sekolah Tinggi Agama Islam Al Hidayah, 2020)
The Yanbu'a method is a tariqah reading and writing and memorizing Al-Qur'an, which was first published in 2004 by the Arwaniyyah Foundation for the Yanbu'ul Qur'an Kuddus Islamic Boarding School. This study aims to describe the use of the Yanbu'a method for the students' reading ability of the Al-Qur'an at Pondok Pesantren Al-Badar Pamijaan Bogor. This research method is quantitative research. The subjects of this study were students of Al-Badar Islamic Boarding School. The data sources of this research were distributing questionnaires to 20 students, interviews with the leaders of the Al-Badar Islamic Boarding School and the Ustadz / ah, the students 'recitation activities, and the results of the students' development achievement cards. The instruments in this study were (1) the students' achievement card to read the Al-Qur'an to gain progress in reading the Al-Qur'an during the use of the Yanbu'a method, (2) a questionnaire test to obtain data on the results of using the Yanbu'a method on their ability. Students read the Qur'an. The results of this study indicate the conclusions (1) The use of the Yanbu'a method at Al-Badar Islamic Boarding School is in a suitable category (2) The ability to read the Al-Qur'an of students at Al-Badar Islamic Boarding School is in the first category (3) There is a positive correlation. The strong or high between the use of the Yanbu'a method on the ability to read the Al-Qur'an of the students at Al-Badar Islamic Boarding School, which is 0.89.